Ball velocity and spin at the impact of tennis serves: Reliability of a ball motion measurement instrument (TRACKMAN) - Sato, B.; Wakatsuki, R.; Kashiwagi, Y.; Funato, K. (Coaching and Sport Science Review, 2017)
To verify the reliability of the precision of TRACKMAN measurements, we analyzed 3 types of serves (flat, slice, kick) and compared the results to values obtained with the 3D motion capture system (VICON). Positive linear strong correlations were observed in velocity calculated with TRACKMAN(x) and VICON(y) ; (r = 0.996, p<0.01), as well as number of ball spin; (r = 0.978, p<0.01). This suggests that ball velocity and the number of ball spin values calculated with TRACKMAN, can provide immediate feedback and is provides sufficient reliability and would be useful in training situations.